Inovasi Sterilisasi Ozon Buah Pir Pasca Panen - Sholihah Ayu Wulandari; Ahmad Fahriyannur Rosyady; Boby Dwi Januarta; Bima Prayoga; Johan Krisbima Abi; Asmiranti Asmiranti (Politeknik Negeri Jember, 2022)
Fruit is the most popular food element of Indonesian people, almost everywhere in Indonesia sells a variety of fruits, one of which is apples sold in various stores, ranging from traditional markets and supermarkets. However, pear sold by traders are not completely sterile from various bacteria on the skin and flesh of pear, another factor buyers hesitate in buying fruit, namely shelf life or durability for how long the fruit. Therefore, research was conducted on fruit sterilizing technology, one of which was obtained was ozone water purifier technology for fruit sterilizing. From this research, we innovated to develop a user-friendly ozone sterilization tool named ozone box. Several tests of this tool are carried out to determine whether it works correctly or not, the first is an endurance test between fruits sterilized with ozone and fruits that are not sterilized with ozone. This resistance test was conducted over several days and showed results that the physical appearance of fruits sterilized using ozone was much fresher compared to fruits that were not sterilized using ozone or washed clean water.